ANALISIS META TREN RISET EMPIRIS PEMASARAN PENDIDIKAN TINGGI TERINDEKS SCOPUS - Gustina (Cross-Border Journal of Business Management, 2026)
The lack of empirical research metadata on the evaluation of higher education marketing using 8P motivates this study. This study aims to describe the evaluation of higher education marketing research based on 8P from 2019-2022 using the Scopus database. This study uses a meta-analysis research type. The results of the content analysis show, namely: 1) empirical research on Higher Education Marketing based on the 8Ps has fluctuated from 2019 to 2022. The highest was in 2020 n = 28 (32%); 2) the type of manuscript is dominated by Article with n = 64 (73%); 3) research design and methods used are dominated by qualitative with n = 23 (26%); 4) the field of Higher Education Marketing based on the 8Ps in Indonesia is dominated by the field of promotion, namely n = 70 (80%). While the few are the price and place fields n = 0 (0%); 5) journal publishers are dominated by the Journal of Marketing for Higher Education n = 13; 6) authors are dominated by Emmanuel Mogaji having 2384 citations with n = 4. Further researchers can study the higher education marketing field, focusing on price and place, which are still little studied by researchers. In addition, explore research methods that are still little studied, such as content analysis and SWOT analysis.